Single-port transperitoneal robotic-assisted laparoscopic radical prostatectomy (spRALP): Initial experience - Yifan Chang; Xiaojun Lu; Qingliang Zhu; Chuanliang Xu; Yinghao Sun; Shancheng Ren (Asian Journal of Urology)
Objective: To assess the feasibility of single-port transperitoneal robotic-assisted laparoscopic radical prostatectomy (spRALP) and discuss its surgical technique. Methods: A 60-year-old male was admitted with an elevated prostate-specific antigen (PSA) level of 13.89 ng/mL and confirmed with prostate cancer on biopsy showing three of 22 positive cores with a Gleason score of 3 + 4 = 7. Multiparametric magnetic resonance (MR) and bone scintigraphy showed organ-confined disease. spRALP was performed using da Vinci Si HD surgical system, with access of a quadri-channel laparoscopic port placed supraumbilically. Two drainage tubes were placed before wound closure. The surgical procedure was largely in consistence with a conventional robotic-assisted laparoscopic radical prostatectomy. Results: The surgery was successfully carried out with a duration of 152 min and an estimated blood loss of 100 mL. The patient was discharged on postoperative Day 4 after removal of both pelvic drainage tubes. Foley catheter was removed on postoperative Day 14. No major complications were encountered. Postoperative pathology showed a Gleason score of 3 + 4 = 7 with no extraprostatic extension and negative surgical margins. Conclusion: Single-port robotic prostatectomy is feasible using the currently available robotic instruments in most Chinese robotic urological centers. Meticulous preoperative planning and careful patient selection are mandatory. Further studies concerning perioperative complications and pentafecta outcome compared with the conventional multi-port robotic prostatectomy is required. Keywords: Laparoendoscopic single-site surgery, Prostate cancer, Robotic surgery, Surgical technique